Structural insights of an LCP protein–LytR–from Streptococcus dysgalactiae subs. dysgalactiae through biophysical and in silico methods - Paquete-Ferreira, João; Freire, Filipe; Fernandes, Henrique S.; Muthukumaran, Jayaraman; Ramos, João; Bryton, Joana; Panjkovich, Alejandro; Svergun, Dmitri; Santos, Marino F. A.; Correia, Márcia A. S.; Fernandes, Alexandra R.; Romão, Maria João; et al. (Frontiers in Chemistry, 2024)
The rise of antibiotic-resistant bacterial strains has become a critical health concern. According to the World Health Organization, the market introduction of new antibiotics is alarmingly sparse, underscoring the need for novel therapeutic targets. The LytR-CpsA-Psr (LCP) family of proteins, which facilitate the insertion of cell wall glycopolymers (CWGPs) like teichoic acids into peptidoglycan, has emerged as a promising target for antibiotic development. LCP proteins are crucial in bacterial adhesion and biofilm formation, making them attractive for disrupting these processes. This study investigated the structural and functional characteristics of the LCP domain of LytR from Streptococcus dysgalactiae subsp. dysgalactiae. The protein structure was solved by X-ray Crystallography at 2.80 Å resolution. Small-angle X-ray scattering (SAXS) data were collected to examine potential conformational differences between the free and ligand-bound forms of the LytR LCP domain. Additionally, docking and molecular dynamics (MD) simulations were used to predict the interactions and conversion of ATP to ADP and AMP. Experimental validation of these predictions was performed using malachite green activity assays. The determined structure of the LCP domain revealed a fold highly similar to those of homologous proteins while SAXS data indicated potential conformational differences between the ligand-free and ligand-bound forms, suggesting a more compact conformation during catalysis, upon ligand binding. Docking and MD simulations predicted that the LytR LCP domain could interact with ADP and ATP and catalyze their conversion to AMP. These predictions were experimentally validated by malachite green activity assays, confirming the protein’s functional versatility. The study provides significant insights into the structural features and functional capabilities of the LCP domain of LytR from S. dysgalactiae subsp. dysgalactiae. These findings pave the way for designing targeted therapies against antibiotic-resistant bacteria and offer strategies to disrupt bacterial biofilm formation.